Comparative Study of Hydrogen Adsorption on Alkali Metal Assisted Carbon-Nano Structured Materials (International Journal of Engineering and Computer Science, 2014)
Using first-principles density functional theory, we have studied the hydrogen storage capacity of alkali metal decorated graphene and carbon nanotubes. Due to curve nature of nanotubes, it shows higher capacity of storing hydrogen than the graphene. We also found that the sodium decorated nano-structure adsorbs more hydrogen molecules than the lithium and potassium decorated systems. The charge transfer from metal to the nanotubes is responsible for the higher hydrogen uptake. The gravimetric density of hydrogen for the alkali metal assisted carbon nanotubes is calculated to be 9.2 wt% to 11.2 wt %.